ANALISIS PERBANDINGAN KINERJA REKSA DANA SAHAM MENGGUNAKAN METODE REWARD TO VARIABILITY (RVAR), REWARD TO VOLATILITY (RVOL), DAN REWARD TO DIVERSIFICATION (RDIV) - , Rafina ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mutual funds are investment product that has been known to the public since 1997 and recently popular as an alternative investment besides personal savings, time deposits, stocks and bonds. Mutual funds are solution for investors, who have funds but do not have enough time or knowledge on the capital market. Many types of mutual fund in Indonesia, investors should choose mutual fund products which are compatible with their investment objectives. Investor should calculate returned gained and the risks to be faced. The problem is the type of indicators that the investor can use as a measure to choose the mutual fund. This research is a case study that discuss about how to measure and evaluate the performance of equity mutual fund with the period 2006-2010. To get the result outperformed equity mutual fund this study using the method of measurement reward to variability (RVAR), reward to volatility (RVOL), and reward to diversification (RDIV). Researcher conducted a study of 10 equity mutual funds which are active in Indonesia with the period of December 31, 2005 until December 31, 2010. Researcher positioning all of the equity mutual funds in accordance with its performance, and compares the performances of the market (IHSG). Then, result of its performance ranked starting from the best until the worst equity mutual fund. The results showed that 9 of 10 equity mutual funds that have examined were outperformed. This research can be used as a reference for investors who want to invest their funds in euity mutual fund, but investors still need to routinely evaluate the portofolio since present performance does not guarantee the future performance.